Forest Trees of Maine : 1908-2008. - Maine Forest Service (COM) ([Place of publication not identified] : Polar Bear & Co, 2009)
In 1908 the Maine Forest Service released a booklet titles Forest Trees of Maine. Now, 100 years later and in its 14th edition, Forest Trees of Maine remains the Maine Forest Service's most popular publication. All editions have had the same objective: to relate accurate information and to keep pace with new findings. The book contains information on 78 different tree species, including all of Maine's commercially important native tree species, as well as a few of the more common and important introduced trees.
Keywords: Trees -- United States -- Identification; Trees -- Identification; Forests and forestry -- Maine; Trees; Trees -- Maine -- Identification